Gone baby gone [videorecording (DVD)] - Affleck, Ben, 1972-; Affleck, Casey, 1975-; Monaghan, Michelle; Freeman, Morgan; Lehane, Dennis (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2008)
Amanda McCready is a 4-year-old who has disappeared from her Boston home. The police make little headway in solving the case, so the girl's aunt hires Patrick Kenzie and Angie Gennaro, private detectives. They freely admit that they have little experience with this type of case, but the family wants them for two reasons: they're not cops and they know the tough neighborhood in which they all live. As the case progresses, Patrick and Angie must face area drug dealers, gangs and pedophiles. When they finally solve the case, they are faced with a moral dilemma that tears them apart.